Stock Market Alerts LLC.: Emerging Stock to Watch: HRAL - February 6, 2008 (M2 Presswire, 2008)
"Airdrie is Calgary's largest suburb with one of the fastest growing populations in Canada," stated Robert J. Oswald, President of HearAtLast. "Airdrie is located on the Queen Elizabeth II Highway, Alberta's busiest thoroughfare linking Calgary to Edmonton. We landed another great location as we continue our expansion in Western Canada," added Oswald. iVoice Technology, Inc. designs, manufactures, and markets innovative Interactive Voice Response (IVR) applications and computer telephony communications systems. On Feb. 5th, the company announced that it signed a non-binding Letter of Intent to acquire Atire Technologies, Inc ("Atire Technologies"). iVoice Technology, Inc. ("iVoice Technology") previously was a wholly owned subsidiary of iVoice, Inc. (OTCBB: IVOI) prior to the spin-off from iVoice that was completed in August 2005 as a special stock dividend distribution to iVoice shareholders. The transaction, which is subject to due diligence, the usual and customary conditions, and entering into a definitive agreement, is expected to close in May 2008. It is anticipated that Atire Technologies will merge into a wholly owned subsidiary of iVoice Technology. This release may contain statements that constitute forward- looking statements within the meaning of Section 27A of the Securities Act of 1933, as amended, and Section 21E the Securities Exchange Act of 1934, as amended. The words "may," "would," "will," "expect," "estimate," "anticipate," "believe," "intend," and similar expressions and variations thereof are intended to identify forward- looking statements.